Effectiveness of unsaturated drainage layer in water diversion under different rainfall conditions - Yunusa, Gambo Haruna (2014)
The concept of capillary barrier principle is widely applied as lasting solution to rainfall infiltration in unsaturated soil slope. However, the performance of a capillary barrier system normally reduced as rainfall duration gets longer, due excessive rainfall infiltration. Therefore this paper uses numerical modeling approach to highlights the effectiveness of a capillary barrier system with unsaturated drainage layer at interface to improve its performance under three different rainfall conditions. The capillary barrier system was constructed using residual soil obtained within the compound of Universiti Teknologi Malaysia, Johor Bahru campus; with sand and gravel employed as unsaturated drainage layer. The system was subjected to rainfall intensities of 1 hour, 1 day and 7 days obtained from Intensity-Duration-Frequency (IDF) curve of Johor Bahru, Malaysia. The results show that high intensity short duration rainfall has less effect on eliminating soil matric suction completely, however the near surface matric suction was eliminated due to prolonged rainfall infiltration and a capillary barrier system constructed with gravel as unsaturated drainage layer is more effective in diverting the infiltrated water before breakthrough occurs under all the rainfall conditions.